The influence of physical activity on the severity of symptoms and well-being of patients with BPD - Serba, Анна; Zubatiuk, Оксана (Psychosomatic Medicine and General Practice, 2025)
Background. Borderline personality disorder (BPD) is one of serious mental illnesses, with the lifetime prevalence reported as 1-4% in the general adult population and about 20% in inpatient psychiatric services. Life expectancy for patients with BPD is about 20 years shorter than for the general population. At the same time, no psychoactive medication has proved its efficacy in the treatment of BPD, and no medication has been officially approved as a treatment of choice in the USA, Europe or the UK, accordingly. More than a half of patients report insufficient effect of psychotherapy, despite the availability of a wide range of approaches. The search of effective treatments for BPD is ongoing in many countries. Objective. The purpose of the research is to analyze the connection between the level of patient’s physical activity (PA) and the severity of BPD symptoms, and to asses the influence of PA on wellbeing of people with BPD. Methods. Three psychodiagnositc methods were used to perform the research: Borderline Evaluation of Severity Over Time (BEST) scale; Global Physical Activity GPAQ questionnaire; RAND 36-Item Health Survey (SF-36) scale. Quantitative methods were used to analyze the results of the research. The research was performed online on the basis of Reddit platform, on the subreddit for people suffering from BPD. 112 community members took part in the research. For the analysis the participants were divided into 2 groups: group 1 with 89 participants whose health is not limited by physical diseases; group 2 with 23 participants who are limited in physical functioning due to their state of health. Results. Statistically significant association (r = 0.208; p < 0.05) was identified between the PA level and points for subscale C (Positive behavior) of BEST in the general group of participants. For group 1 the analysis revealed a statistically significant positive association (r = 0.221; p < 0.05) between the PA level and points for C (Positive behavior) subscale (r = 0.221; p < 0.05) and A (Thoughts and feelings) subscale (r = 0,195; p = 0,0489) of BEST. For group 2 the analysis revealed a statistically significant negative association between the PA level and points for A (Thoughts and feelings) subscale (r = -0.678; p < 0.05) and B (Negative behavior) subscale (r = -0.724; p < 0.005) of BEST. Also, it was found out that PA level has a statistically significant negative association (r = -0.712; p < 0.05) with the severity of symptoms for these participants. A statistically significant positive association (r = 0,193; p < 0.05) has been discovered between the PA level and the quality of live according to Physical functioning subscale of RAND SF-36. Connection between PA level and severity of BPD symptoms, as well as connection between PA level and the points for subscales that asses the symptoms by domains are different for the groups. The result for the general group suggests that an active way of living may stimulate positive behavior. For those participants who are not limited in physical functioning as the result of their physical health an active way of living may stimulate positive behavior patterns but at the same time enhance negative thoughts and feelings. The most significant positive effect of PA was identified for the participants who are significantly or slightly limited in their physical functioning due to their somatic diseases. In this case an active way of living decreases the level of negative thoughts, feelings and negative behavior and also decreases the general severity of BPD symptoms. Conclusions. In regards to the assumption that PA may support and enhance healthy lifestyle and positive behavior, and, in some cases, decrease the negative behavior and severity of BPD symptoms in general, using PA as an element of treatment programs for people with BPD seems considerable. Existing individual therapy model must be taken into consideration, as well as patient’s expectations, needs and health conditions. Keywords: quality of life, borderline personality disorder, physical activity, psychological support programs for people with BPD.